The efficacy of venlafaxine on depressive symptoms of patients diagnosed with both alcohol use disorder and major depressive disorder - Kalyoncu, Ö. Ayhan; Mırsal, Hasan; Pektaş, Özkan; Tan, Devran; Beyazyürek, Mansur (Journal of Dependence, 2007)
Objective: The aim of our study was to determine the efficacy of venlafaxine on depressive symptoms of patients diagnosed with both alcohol use disorder and major depressive disorder.Method: Patients with a diagnosis of both alcohol use disorder and MDD (Major Depressive Disorder) according to DSM-IV criteria, baseline Hamilton Depression Scale (HAM-D) scores of minimum 14 at first evaluation, abstinence from alcohol for at least 2 weeks and an age between 18 – 65 years were enrolled to the study. In the first week of the study, venlafaxine XR was administered at 75 mg/day. In the second week the dosage was increased to 150 mg/day which was the accepted treatment dosage. Hamilton Anxiety Scale (HAM-A), HAM-D, Clinical Glogal Impression Scale (CGI) and Symptom Check List (SCL-90-R) tests were applied to the patients. The patients were evaluated prior to study and on days –1, 8, 15, 22, 29, 43 and 57 of drug treatment.Results: A total of 61 patients were screened for the study. As a result, 59 patients were included in the first visit and 4 of these patients discontinued the study. The reasons for discontinuation were: increase of depressive symptoms in two cases; one case manic shift; resumption of alcohol use in one case. HAM-D, HAM-A and SCL-90-R total scores decreased during the treatment period and this decrease was also statistically significant.Conclusion: Our results suggest significant improvement in depression and anxiety symptoms during venlafaxine XR treatment in patients diagnosed with both alcohol use disorder and major depressive disorder.
Keywords: Venlafaxine; depression; alcohol dependence; efficacy